Biaxial Equatorial Solar Tracker with High Precision and Low Consumption: Modelling and Realization - Hicham Bouzakri; Ahmed Abbou; Khalil Tijani; Zakaria Abousserhane (International Journal of Photoenergy, 2021)
The solar tracker is a mechanism that helps the photovoltaic panel to maximize its performance, while keeping it oriented towards direct solar radiation. In order to specify tracking, most solar trackers use two axes, one horizontal and the other vertical, which implies an increase of the consumed energy and a decrease in precision, since we have to make both motors operate simultaneously. This paper is a modelling of a biaxial solar tracker, with the principle of an equatorial mount, allowing it to precisely follow the sun via a single axis (equatorial axis), while the second axis (tilt axis) makes a small daily correction of few seconds at sunrise. In this way, our model keeps precision to the maximum, with minimum energy consumption. A detailed simulation clearly shows that the proposed model receives the maximum solar irradiation that a normal surface to solar radiation can receive and may in a certain period of the year receive a gain in the amount of solar irradiation; we have up to 63.47% compared to a fixed installation. The study details the different tracking methods, in order to adapt the concept model to the type of solar panel used. We closed finish the study with the realization of the prototype with a detailed explanation of the concept movement. To validate the simulation, we have made an experience that gives us the same results as given by simulation.